Agronomic and nutritional characteristics of three buckwheat cultivars under organic farming in three environments of the Garfagnana mountain district - Ghiselli, Lisetta; Tallarico, Remigio; Mariotti, Marco; Romagnoli, Sigfrido; Baglio, Adriano P.; Donnarumma, Pasquale; Benedettelli, Stefano (Italian Journal of Agronomy, 2016)
Buckwheat is a crop that has virtually disappeared in Italy, and products are generally imported from Poland and China. Among the alternative crops, suitable for cultivation in marginal areas and mountain foothills, buckwheat is particularly adapted as it is a rustic crop that can be grown without chemical input. Buckwheat is rich in numerous functional components and is, therefore, suitable for the obtaining of health products. The aim of the present research was to evaluate the adaptability of three cultivars of buckwheat (Fagopyrum esculentum Moench) grown under organic management at different altitudes in the mountain district of Garfagnana (Tuscany, Italy). The main biometric and production parameters were measured. Protein, macroand microelement and total polyphenol contents were determined in the grain. Significant differences for most parameters were evident for the different environments; some biometric parameters were also different among cultivars. All genotypes were suitable for cultivation in the Garfagnana district based on yield and biometric data. Mineral element content was useful for the characterisation of geographic origin.